1993
DOI: 10.1002/ajim.4700230407
|View full text |Cite
|
Sign up to set email alerts
|

Selected health risks caused by long‐term, whole‐body vibration

Abstract: The problem of a "vibration disease" caused by low-frequency whole-body vibration (wbv) is critically discussed. Disorders of the nervous, circulatory, and digestive systems are interpreted not to be predominantly wbv-specific, but to be related to the totality of working conditions. Long-term wbv exposure can probably contribute to the pathogenesis of disorders of female reproductive organs (menstrual disturbances, anomalies of position) and disturbances of pregnancy (abortions, stillbirths). Animal experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 34 publications
(16 reference statements)
2
72
0
4
Order By: Relevance
“…Some studies have shown that WBV also has effects on the digestive system, female reproductive organs and peripheral veins. Long-term WBV exposure can contribute to the pathogenesis of disorders of the female reproductive organs (menstrual disturbances, anomalies of position) and disturbances of pregnancy (abortions, stillbirths) (Seidel 1993;Lings and Leboeuf-Yde 2000). To prevent these potentially dangerous side effects, it is important to consider safe exercise protocols when developing exercise programs for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that WBV also has effects on the digestive system, female reproductive organs and peripheral veins. Long-term WBV exposure can contribute to the pathogenesis of disorders of the female reproductive organs (menstrual disturbances, anomalies of position) and disturbances of pregnancy (abortions, stillbirths) (Seidel 1993;Lings and Leboeuf-Yde 2000). To prevent these potentially dangerous side effects, it is important to consider safe exercise protocols when developing exercise programs for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated, long term exposure to WBV, such as in the workplace, has been shown to have detrimental effects on the body (48). However, it has been suggested that short term exposure to WBV may have beneficial effects on the body, in both men and women.…”
Section: Whole Body Vibrationmentioning
confidence: 99%
“…The individual effects of the strain depend on the strength of spinal structure and their ability to recover from a repetitive load. The strength of vertebrae was shown to be a function of their size, mineral content and age [3,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the effect of long-term whole-body vibration exposure on spinal health has been found to vary considerably [1][2][3]. The whole-body vibration exposure was described by the accelerations mainly measured at the interface between the driver and his seat cushion.…”
Section: Introductionmentioning
confidence: 99%